Japanese diplomacy and global affairs in 2004 (Tokyo, 2005)
Diplomatic Bluebook will help to provide you with a deeper understanding of the international situation and Japan’s diplomacy as well as the Foreign Ministry. Based on the fundamental awareness that Japan has a duty to play an important role in the international community, the government of Japan is determined to exhibit leadership in resolving problems facing the international community again in 2005, promoting diplomacy with integrity based on Japan’s national interest.
Keywords: Nhật Bản,Japan; Quan hệ ngoại giao,Foreign relations